Blockchain development for finance projects : building next-generation financial applications using Ethereum, Hyperledger Fabric, and Stellar - Roy, Ishan (Packt Publishing, 2020)
Blockchain technology will play a disruptive role in the banking and finance sector in the future. Experts estimate that it will save up to 20 billion dollars annually. You will build full-fledged financial applications using blockchain. It will aid you in building more secure and transparent workflows and re-engineering your business processes.